Pengaruh Likuiditas, Audit Tenure, dan Ukuran Perusahaan Terhadap Opini Audit Going Concern pada Perusahaan Manufaktur - Azhari Muhammad Irfan; Ahmad Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Going concern audit opinion is the giving of the auditor's opinion on the condition of the company that is doubtful about its survival (going concern). This study aims to examine the effect of liquidity, audit tenure, and firm size on going-concern audit opinion. This type of research is quantitative research conducted at manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The sampling technique uses purposive sampling method. So that there were 17 companies from a total of 144 manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017. The data used is secondary data by testing using logistic regression analysis. The results of this study indicate that liquidity affects the going concern audit opinion. While the audit tenure and company size do not affect the going-concern audit opinion.